2003
DOI: 10.1034/j.1600-051x.2003.20004.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a new mouthrinse containing chlorhexidine, cetylpyridinium chloride and zinc lactate on the microflora of oral halitosis patients: a dual‐centre, double‐blind placebo‐controlled study

Abstract: The test mouthwash demonstrated efficacy in reducing the microbiological parameters in three oral niches in moderate to severe halitosis patients without periodontitis, and this was correlated with the improvements in organoleptic and VSC scores but not with the tongue coating scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 33 publications
5
120
0
9
Order By: Relevance
“…1,28,29,30,31,32 Researchers have been able to find positive correlations between tongue coating status (amount and or presence) and the different parameters directly related with oral malodor. In this scenario, the tongue becomes the most important microenvironment to study and to target in the prevention and treatment of oral halitosis and also as a potential reservoir for periodontal pathogens.…”
Section: Mechanical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…1,28,29,30,31,32 Researchers have been able to find positive correlations between tongue coating status (amount and or presence) and the different parameters directly related with oral malodor. In this scenario, the tongue becomes the most important microenvironment to study and to target in the prevention and treatment of oral halitosis and also as a potential reservoir for periodontal pathogens.…”
Section: Mechanical Approachmentioning
confidence: 99%
“…The morphology of the dorsum of the tongue provides additional irregularities such as fissures, grooves and depapillated areas that may serve as retention areas for harboring bacteria. 1,29,33,34 The development of a predominant anaerobic microbiota associated with tongue coating has been considered an ideal microenvironment to produce malodorous compounds, and therefore different authors have tried to assess the relationship between the morphology of the tongue and the severity of oral halitosis. 35,36 Numerous studies have found a relationship between the mechanical removal of tongue coating and the reduction of both organoleptic scores and VSC levels, including reduction in methyl mercaptan levels and the methyl mercaptan/hydrogen sulfide ratio, in both healthy and periodontitis patients, with or without halitosis.…”
Section: Mechanical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have implicated the dorsum of the tongue as the primary source of volatile sulphur compound (VSC), both in periodontally diseased and healthy individuals 2,18,19 . Mechanical reduction of malodor and of the intraoral bacterial count may be achieved by disrupting the tongue biofilm, thus decreasing the production of VSCs and other volatile organic compounds 20 .…”
Section: Reduction In Total Load Of Oral Microorganisms and Or Bactermentioning
confidence: 99%
“…Other chemical agents can reduce halitosis by chemically neutralizing VSCs. The active ingredients in these products are most commonly zinc and chlorine dioxide [48]. Metal ions with a high affinity for sulfur inhibit the formation of VSCs, which is likely also related to the antibacterial properties of the metal [49,50].…”
Section: Basic Therapeutic Approachmentioning
confidence: 99%